Socio-economic analysis of municipal fishing in selected barangays of Banate, Iloilo - Bayani, Marie Joy Gesulgon
The main objectives of the study were to determine the social and economic characteristics of municipal fishermen, costs structure, profitability level, and problems encountered by municipal fishermen in Banate Iloilo., The study made used of cost and return analysis to determine the economic condition of the respondents. This study covered the municipal fishermen of selected barangays of Banate. The study was dependent on the data given by the respondents and not all data maybe reliable. The assumption that changes in effort and adjustment in fishing stocks were taken into consideration. The findings of the study showed that 93.75 of the fisherman respondents were dependent on fishing for their livelihood. All the fishermen except the hook and line operators could not be considered as absolute poor as their income compared to the poverty threshold. The cost and return analysis of the study showed that fish corral operators incurred the lowest opportunity cost amounted to PHP 31.47 while crab pot registered the highest opportunity cost of PHP 48.39. Set gillnet incurred the highest variable cost of PHP 80.62 per trip. Crab pot incurred the highest fixed cost amounted to PHP 56.0 per trip. In profit, crab incurred the highest gross profit with PHP 380.58 and hook and line registered the lowest gross profit of PHP 1.30 per trip. As expected crab pot incurred the highest net profit of PHP 276.19 per trip. Moreover in all profitability indices, crab pot, push net, and set gillnet posted positive receipts. Fish corral and hook and line incurred negative profitability indices. the variations in the results can be attributed to the difference in gears used by the respondents, average trip per week, average hour per trip, percentage of motorized and non-motorized boats, and the average volume of catch per trip. The most common problem faced by the respondents was the presence of illegal fishing in their area. In line with the goals to increase the productivity and welfare of the small-scale fisherman in Banate, the government should give support and assistance in order to upgrade the living condition of the municipal fishermen.